Crop diversification options to improve farmers' livelihoods in Madagascar lowlands - CGIAR Research Program on Rice (2021)
28 vegetables and legumes species imported from WorldVeg, Taiwan and were tested along with 50 local vegetable and legume checks in the year 2018 before rice season (July to December). 12 promising leafy, tuber, grain and fruit vegetables were further tested and the five suitable spp. were identified in Madagascar.